Relationships on Residential Care - Temperament of children in residential care and perceived acceptance/rejection and style of discipline used by care workers - Gaitán, Sabina D.; Fernández-Sánchez, Joanna; Fernández-Baena, Francisco Javier; Salas-Martínez, María Dolores (My University, 2025)
The ability to adapt interpersonal interactions to temperamental characteristics is essential for high-quality care. The present study seeks to deepen our understanding of the reciprocal relationships between the caregivers’ discipline styles and the temperament of the youth in Residential Care. Specifically, it aims to find out whether different temperamental characteristics in reactivity and self-regulation are related to and/or can predict the care workers’ discipline styles and the affective relationships they maintain with the children. A total of 144 children aged 9–16 years (42.6% boys) and their caregivers from 22 residential care homes (Spain) participated.
Keywords: Cuidadores - Aspectos psicológicos - Congresos; Residential Care; Temperament; Acceptance; Rejection; Discipline Style